(untitled) (Research, Society and Development, 2026)
Objective: To identify and characterize the economic impact and usage profile of zirconium cyclosilicate (ZCS) in the management of hyperkalemia in a public hospital in Salvador. Methods: This was a cross-sectional and descriptive study, conducted after the incorporation of CSZ, evaluating the usage profile, effectiveness in reducing serum potassium, and cost-effectiveness of the therapeutic regimens used between March 2023 and March 2025. Patients treated with CSZ, calcium polystyrene sulfonate (CPS), and alternative therapies (furosemide, potassium exchange solution, and bicarbonate solution) were analyzed. Results: 210 patients were evaluated, with 56 treated with CSZ, 50 with CPS, and 104 with alternative therapies. The most prevalent comorbidities were systemic arterial hypertension (75%), type II diabetes mellitus (50%), and chronic kidney disease (44%). The mean age was 59 years, with the highest mean in the CSZ group (68 years). CSZ showed a statistically significant reduction in serum potassium levels after 48 hours of treatment (77%), a greater mean reduction in K⁺ (17.8% ± 9.9), and a lower incidence of persistent hyperkalemia (7.2%). In the economic analysis, CSZ presented a lower mean treatment cost compared to CPS (US 26.05 versus US 31.95), as well as a better cost-effectiveness ratio for achieving normokalemia (US 33.64 versus US 69.33). Conclusions: CSZ demonstrated greater clinical effectiveness and lower cost compared to CPS, contributing to the optimization of hyperkalemia management and better management of public resources in the evaluated institution.